Association between macronutrient intake and amyotrophic lateral sclerosis prognosis. (2nd January 2020) - Kim, Boeun; Jin, Youri; Kim, Seung Hyun; Park, Yongsoon
Abstract : Objectives: Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease, and the nutritional state of ALS patients is associated with survival. The purpose of the present study was to investigate whether macronutrient intake at early stage of the disease was positively associated with survival and duration from symptom onset to death, tracheostomy, or non-invasive ventilation (NIV) in ALS. Methods: ALS patients diagnosed according to EI Escorial criteria were recruited from 2011 to 2016 and followed up until 2017, when they reached the endpoint of death, tracheostomy, or NIV use. Dietary intake was estimated based on a 24-hour recall conducted less than 2 years from symptom onset, and the survival time was defined as the duration from symptom onset to the endpoint. Results: ALS patients were categorized as short-term group ( n =79) and long-term group ( n =69) according to the mean survival time (33.03±14.01 months). Short-term survival was negatively associated with fat, protein, and meat intake, and positively associated with carbohydrate intake after adjustment for confounders. In addition, the survival time was positively associated with fat, protein, and meat intake but was not associated with carbohydrate intake. Discussion: The present study suggested that higher intake of fat and protein, particularly from meat at early stage of the disease, could prolong the survival of ALS patients. However, further clinical trials are necessary to confirm the beneficial effects of higher fat and protein intake on mortality in ALS patients.